Uncertainty, risk, and capital growth - Gill Segal; Ivan Shaliastovich (Leibniz Institute for Financial Research SAFE, 2023)
We find that high macroeconomic uncertainty is associated with greater accumulation of physical capital, despite a reduction in investment and valuations. To reconcile this puzzling evidence, we show that uncertainty predicts lower depreciation and utilization of existing capital, which dominates the investment slowdown. Motivated by these dynamics, we develop a quantitative production-based model in which firms implement precautionary savings through reducing utilization rather than raising investment. Through this novel intensive-margin mechanism, uncertainty shocks command a quarter of the equity premium in general equilibrium, while flexibility in utilization adjustments helps explain uncertainty risk exposures in the cross-section of industry returns.
Keywords: G12; E32; D81; D50; 330; Uncertainty; Production; Asset Pricing; Utilization; Depreciation; Equity Premium